CREATIVE COMMUNITY-BASED TOURISM MANAGEMENT MODEL OF BAN NONG WILAI COMMUNITY, UBON RATCHATHANI PROVINCE - Somnuek, Pariwat (Journal of MCU Nakhondhat, 2025)
The research aimed to 1) Assess the community’s tourism potential, 2) Develop a process for building knowledge in creative community tourism management for the community, and 3) Propose an appropriate creative community tourism management model for the community. This research was a mixed-methods study. The sample consisted of 400 people who had visited the community, selected by convenience sampling. Data were collected using a questionnaire and analyzed using percentages, means, and standard deviations. Thirty key informants were the community committee, homestay group representatives, and representatives of Khemmarat Subdistrict Municipality, using purposive sampling. Data were collected using in-depth interviews and focus group discussion techniques, and descriptive content analysis. The research results revealed that 1) The overall community’s tourism potential was at a high level, except for community organization and community participation, which had a moderate tourism potential. 2) The development of a process for building knowledge in creative community tourism management for the community used a participatory process with community representatives, with experts in creative economy model management providing advice on effective practices, as well as organizing workshops, study visits at model communities for creative economy tourism management, experimenting with their own models, and summarizing lessons learned. And the creative community tourism management model that is appropriate for the community is the food cultural tourism model that is unique to the locality in terms of the ingredients used for cooking and cooking techniques. Currently, the community has adapted it to suit the popularity of tourists by organizing a food tourism model every Saturday evening in the community walking street area.